Platelet count in 100 cases of pregnancy induced hypertension - Rahim, R; Nahar, K; Khan, IA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):5-9. The abstract of this article is available on the PubMed website